Impact of Silicon Content within Silicon-Graphite Anodes on Performance and Li Concentration Profiles of Li-Ion Cells using Neutron Depth Profiling. Issue 2 (8th February 2021) - Moyassari, Erfan; Streck, Luiza; Paul, Neelima; Trunk, Markus; Neagu, Robert; Chang, Chia-Chin; Hou, Shang-Chieh; Märkisch, Bastian; Gilles, Ralph; Jossen, Andreas
Abstract : Due to its high specific capacity, silicon is a promising candidate to substitute conventional graphite as anode material in lithium-ion batteries. However, pure silicon-based anodes suffer from poor capacity retention, mainly due to a large volume change during cycling, which results in material pulverization and other side reactions. Therefore, alternative compositions with lowered silicon content and a similar working voltage as graphite are favored, e.g. silicon-graphite (SiG), as they can reduce these volume change and side reactions while maintaining a high capacity. Here, neutron depth profiling (NDP) offers the unique possibility to quantify non-destructively the lithium concentration profile over the depth of these electrodes. In this study, the (de-)intercalation phenomena during (de-)lithiation in SiG porous anodes with silicon contents ranging from 0 wt% to 20 wt% is investigated for the first time using ex situ NDP during the initial discharge at defined depths of discharge (DODs) states. These findings are complemented by a conventional electrochemical analysis of the first full cycle with a charge/discharge rate of C/20. While the specific capacity is observed to increase with higher silicon content, NDP directly reveals a homogeneous irreversible lithium accumulation within the entire electrode depth.